PENGARUH TAX AVOIDANCE TERHADAP COST OF DEBT DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE 2019-2021 - Arief Sinaga (Universitas Sam Ratulangi, 2023)
Tax avoidance is part of tax planning activities. Tax avoidance use to minimize tax liabilities by utilizing regulatory tax provisions that done legally. Taxpayers may use various strategies to avoid taxes, including deductible expense. This provision provide that interest payment is deductible expense so it may reduce taxable income, and the final goal is to reduce tax payment. The aim of this research is to test about tax avoidance towards cost of debt and institusional ownership as moderating variable. The dependent variable in the study was the cost of debt. Independent variable research is the tax avoidance, measured by proxi the Current Effective Tax Rate (ETR). Population in this research is manufacture firms registered to Bursary Effect of Indonesia (BEI) in 2019-2021 time periods. The amount of sample used is 34 firms collected with purposive sampling. Data program using SPSS (Statistical Product and Service Solution) version 25. Analysis method used in this research is Moderated Regression Analysis (MRA). This research results showing that tax avoidance variable influence to cost of debt. Institusional ownership is has influence as moderating variable to tax avoidance and cost of debt.